The Effect of Pedagogical Competence and Achievement Motivation on Teacher Performance with Organizational Commitment as a Mediating Variable at State Junior High School Sub-Rayon 02 in Jepara Regency - Edi Yulianto; Noor Hudallah; Arief Yulianto; Yeri Sutopo; Nina Oktarina (Educational Management, 2025)
This study aims to analyze the effect of pedagogical competence and achievement motivation on teacher performance, with organizational commitment as a mediating variable at SMP Negeri Sub Rayon 02, Jepara Regency. Using a quantitative approach and path analysis based on survey data from teachers, the results show that pedagogical competence and achievement motivation have a significant direct effect on teacher performance. In addition, achievement motivation also has a positive and significant effect on organizational commitment, which in turn improves teacher performance confirming the role of organizational commitment as an effective mediator in this relationship. However, pedagogical competence does not have a significant effect on organizational commitment, so there is no mediating effect in this pathway. The R² value of 0.754 on teacher performance indicates that the model has high explanatory power. These findings have important implications for teacher development policies, whereby improving performance is not only achieved through technical (pedagogical) training, but also requires strengthening psychological aspects such as achievement motivation and the formation of organizational commitment through transformational leadership, performance-based rewards, and a supportive work climate.